Gaya Bahasa Penyiar Program Cipaganti Dalam Menarik Minat Pendengar - Indriani, Tita -; Sumadiria, AS Haris; Paryati, Paryati (Annaba: Jurnal Ilmu Jurnalistik, 2020)
This study aims to find out (1) the delivery language of the cipaganti program announcer (2) how the cipaganti program announcers set the timing to insert humor, (3) the way the cipaganti program announcer regulates articulation while broadcasting on Ardan Radio 105.9 FM. This research method uses descriptive qualitative study method with data collection techniques in the form of interviews, observations and literature review. The results of the study show as follows, First in terms of the language of broadcast delivery, the "Cipaganti" program uses non-formal (everyday) language styles, while the variety of languages used is Casual Style (Ragam Santai). Second, in the broadcast process, broadcasters include creative elements in the sentence structure of the broadcast language style, such as humor or light jokes. Third, in the broadcasting process, the three broadcasters have different voice characters which are obtained by practicing articulation, namely by reading a lot so that voice characters can be formed.